Film review: ON BODY AND SOUL (Ildikó Enyedi). HU 2017 Film review: ON BODY AND SOUL (Ildikó Enyedi) - Charles Martig (Journal for Religion, Film and Media, 2017)
Interview with Ildikó Enyedi, directrice of ON BODY AND SOUL (HU 2017)